A microfluidic sensor for dynamic surface tension measurement - Nguyen, Nam-Trung (2012)
A novel microfluidic sensor for measuring dynamic gas-liquid interfacial tension is reported. The device consists of a microfluidic chip with a microchannel network and an optical detection system. The sample is introduced into a main channel, while air is injected through a T-junction. Owing to the fixed flow rate ratio used for the sensor, surface tension is the only parameter determining bubble formation frequency, which can be measured by optical detection. Although the bubble is represented by a pulse in the output signal, the formation frequency is simply the frequency of the output signal. Measurements were carried out for aqueous solutions with different concentrations of the ionic surfactant cetyl trimethyl ammonium bromide. Surface tensions of these solutions were calibrated with a commercial tensiometer. The measurement results show a clear relationship between surface tension and formation frequency. The sensor can be used to identify the critical micelle concentration of the surfactant. The sensor potentially allows the use of a minute amount of sample compared with the relatively large amount required for existing commercial systems.